The let them theory ebook A life-changing tool that millions of people can't stop talking about. - Robbins, Mel (2024)
#1 New York Times Bestseller #1 Sunday Times Bestseller #1 Amazon Bestseller #1 Audible Bestseller A Life-Changing Tool Millions of People Can’t Stop Talking About What if the key to happiness, success, and love was as simple as two words? If you've ever felt stuck, overwhelmed, or frustrated with where you are, the problem isn't you. The problem is the power you give to other people. Two simple words— Let Them —will set you free. Free from the opinions, drama, and judgments of others. Free from the exhausting cycle of trying to manage everything and everyone around you. The Let Them Theory puts the power to create a life you love back in your hands—and this book will show you exactly how to do it. In her latest groundbreaking book, The Let Them Theory , Mel Robbins— New York Times bestselling author and one of the world's most respected experts on motivation, confidence, and mindset—teaches you how to stop wasting energy on what you can't control and start focusing on what truly matters: YOU. Your happiness. Your goals. Your life. Using the same no-nonsense, science-backed approach that's made The Mel Robbins Podcast a global sensation, Robbins explains why The Let Them Theory is already loved by millions and how you can apply it in eight key areas of your life to make the biggest impact. Within a few pages, you'll realize how much energy and time you've been wasting trying to control the wrong things—at work, in relationships, and in pursuing your goals—and how this is keeping you from the happiness and success you deserve. Written as an easy-to-understand guide, Robbins shares relatable stories from her own life, highlights key takeaways, relevant research and introduces you to world-renowned experts in psychology, neuroscience, relationships, happiness, and ancient wisdom who champion The Let Them Theory every step of the way. Learn how to: Stop wasting energy on things you can't control Stop comparing yourself to other people Break free from fear and self-doubt Release the grip of people's expectations Build the best friendships of your life Create the love you deserve Pursue what truly matters to you with confidence Build resilience against everyday stressors and distractions Define your own path to success, joy, and fulfillment . . . and so much more. The Let Them Theory will forever change the way you think about relationships, control, and personal power. Whether you want to advance your career, motivate others to change, take creative risks, find deeper connections, build better habits, start a new chapter, or simply create more happiness in your life and relationships, this book gives you the mindset and tools to unlock your full potential. Order your copy of The Let Them Theory now and discover how much power you truly have. It all begins with two simple words. The cover has been updated to include the name of co-author Sawyer Robbins. Customers may receive either version of the cover at random.